Exploring the impact of virtual reality-based mathematics learning on students’ motivation: Protocol for a systematic review and meta-analysis - Shally Novita; Hari Setyowibowo; Puspita Adhi Kusuma Wijayanti; Wina Erwina; Whisnu Yudiana; Fredrick Dermawan Purba; Afra Hafny Noer (PLoS ONE, 2025)
It has been extensively documented that motivation plays a pivotal role in both the learning and performance of mathematics, often intersecting with various antecedents of mathematical competence, such as math anxiety and self-esteem. These factors, in turn, significantly influence the well-being of students. Therefore, it is necessary to provide learning situations that may impact students’ motivation in learning mathematics. During the digital era, studies have examined the use of technology, particularly, virtual reality-based mathematics learning in explaining the variance of students’ motivation in mathematics learning. However, the results seem to be various and a comprehensive review about the impact of virtual reality mathematics learning on students’ motivation does not seem to exist yet. This review aims to fill this knowledge gap by examining the impact of mathematics learning using virtual reality-based learning materials on students’ motivation. The literature search will be conducted across multiple bibliographic databases, including Cambridge, Oxford, PubMed, Science Direct, Scopus, SpringerLink. Only studies published in English, German, or Indonesian within the past seven years will be eligible for inclusion in the review. The risk of bias inherent in this review will be evaluated by two independent reviewers utilizing the Joanna Briggs Institute (JBI) critical assessment tool. Any discrepancies between the reviewers will be resolved through the third reviewer. Further, quality of evidence will be examined using The Grading of Recommendations, Assessment, Development, and Evaluations (GRADE). A review exploring the correlation between mathematics education utilizing virtual reality and student motivation will offer educational practitioners and stakeholder’s valuable insights into the effective integration of technology-based learning resources, particularly virtual reality. The findings of this study aim to elucidate the advantages and potential drawbacks associated with the adoption of virtual reality in mathematics education, as well as identify the student and instructional material characteristics that may be associated with specific increases in motivation. This protocol has been registered in PROSPERO with registration number: CRD42023463974.